Early-stage endometrioid carcinoma with MSH6 protein deficiency: pitfalls in the diagnostic interpretation of microsatellite instability - Wang, Cheng; Liang, Dongni; Wang, Wei; Kuang, Wei; Zou, Juan; Zeng, Jing; Feng, Min (Frontiers in Oncology, 2025)
ObjectiveMicrosatellite instability (MSI)/mismatch repair (MMR) protein testing is important for Lynch syndrome (LS) identification, prognostic stratification, and immune checkpoint inhibitor screening in many solid malignancies. MSH6, an MMR protein, is less studied in LS, and the exact mechanism of inconsistent MSI and MMR results among endometrial cancer (EC) patients who are carriers of MSH6 mutations remains unclear. The aim of this study was to identify the molecular patterns and clinicopathological characteristics of MSH6 protein-deficient LS-related EC and to further investigate possible causes of discordant MSI and IHC results in MSH6 variant carriers.MethodsTwenty-seven patients who were diagnosed with EC with only MSH6 protein deficiency from 2021 to 2023 at West China Second University Hospital were enrolled. PCR capillary electrophoresis (PCR-CE) was performed in all cases and further next-generation sequencing (NGS) was performed in non-MSI-high cases. Data on immunohistochemistry (IHC) markers, microsatellite shift patterns, and molecular profiles were further reviewed by an experienced molecular pathologist.ResultsAmong the 27 patients, 14 (51.9%) cases were found to be non-MSI-high, while only 8 of 14 (57%) cases successfully underwent NGS and ultimately incorporated into our study. All patients who were MSH6 protein negative were diagnosed with early-stage endometrioid carcinoma (EC), with a median age of 55 years (range 48–67 years). We reanalyzed the shift of all microsatellite loci and found one case with an additional unstable locus. Minimal microsatellite shifts (one to three nucleotide shift) were observed in all cases (100%), which occurred in mononucleotide markers from BAT 25 or BAT 26. Nevertheless, 3 of the 8 patients (37.5%) displayed MSI-H by NGS, which revealed truncating mutations in the MSH6 gene in exon 4 in 62.5% (5/8) of the patients, including nonsense mutations (37.5%), frameshift insertions (12.5%), and frameshift deletions (12.5%). The proportion of cases correctly classified (as determined via IHC markers) by MMR genomic status was greater (100%) than that correctly classified by PCR-CE (12.5%) in cases of MSH6 truncating variation. In addition, NGS (37.5%) had a higher MSI-H detection rate than PCR-CE (12.5%) in evaluating MSI status.ConclusionCarriers of a germline pathogenic MSH6 variant are more likely to develop EC at an advanced age, and a non-MSI-H phenotype with minimal microsatellite shift is frequently observed only when the MSH6 protein is lost. This atypical MSI pattern is often overlooked, potentially increasing the risk of underdiagnosis of LS.